Expression profiling of IL‐10‐regulated genes in human monocytes and peripheral blood mononuclear cells from psoriatic patients during IL‐10 therapy - Mechthild Jung; Robert Sabat; Jörn Krätzschmar; Henrik Seidel; Kerstin Wolk; Christiane Schönbein; Sabine Schütt; Markus Friedrich; Wolf‐Dietrich Döcke; Khusru Asadullah; Hans‐Dieter Volk; Gerald Grütz (2004)
Abstract Interleukin‐10 (IL‐10), originally identified as an inhibitor of pro‐inflammatory cytokine production, exerts multiple immunomodulatory functions. Its ability to inhibit a Th1 response has been used in clinical trials for the treatment of inflammatory diseases including psoriasis. However, little is known about the molecular mechanisms of IL‐10 functions. We aimed at identifying possiblemediators of in vitro IL‐10 treatment in monocytes by gene chip technology using Hu95a Affymetrix mRNA arrays with 12,000 genes. To prove relevance of the identified genes for the clinicalsituation we compared these in vitro results with genes being regulated by IL‐10 in peripheral blood mononuclear cells from psoriatic patients undergoing IL‐10 therapy. A high proportion of the 1,600 genes up‐regulated and 1,300 genes down‐regulated in vitro was found to be similarly regulated in vivo . Some genes, which were previously unknown to be regulated by IL‐10, can be assigned to known IL‐10 functions like e.g. the increase of pathogen clearance. Other new potentially immunomodulating genes have been identified to be regulated by IL‐10, but their impact needs to be experimentally evaluated. We could confirm a recently reported up‐regulation of heme oxygenase‐1 (HO‐1). However, we demonstrate that the anti‐inflammatory mechanisms of IL‐10 remain functional even when HO‐1 is irreversibly inhibited.